2008
DOI: 10.1002/pssc.200779112
|View full text |Cite
|
Sign up to set email alerts
|

Surface strain contributions to the lineshapes of reflectance difference spectra for one‐electron and discrete‐exciton transitions

Abstract: Reflectance difference spectroscopy (RDS/RAS) constitutes a very sensitive tool for the study of the optical properties of semiconductors. RDS spectra comprise several components of different physical origins. One of these components is the strain induced by the surface. In the present work, we report RD spectra measured on GaAs at room temperature at around E1 and the E1+Δ1 transitions. Two cases were studied, the surface strains induced by the c (4× 4) reconstruction and by the vacancies generated by the ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For instance, the roughness and diffusion gradients of As or vacancies introduced during the growth process are in general different for the upper and lower interfaces of each layer. It is known that As vacancies and their gradient distribution through the QW generates an anisotropic strain field at the interfaces [18]. The relative orientation of these fields at the upper and lower interfaces of a QW is rotated by 90 • around the [001] axis, thus leading to optical anisotropies with opposite signs.…”
Section: Modelmentioning
confidence: 99%
“…For instance, the roughness and diffusion gradients of As or vacancies introduced during the growth process are in general different for the upper and lower interfaces of each layer. It is known that As vacancies and their gradient distribution through the QW generates an anisotropic strain field at the interfaces [18]. The relative orientation of these fields at the upper and lower interfaces of a QW is rotated by 90 • around the [001] axis, thus leading to optical anisotropies with opposite signs.…”
Section: Modelmentioning
confidence: 99%
“…At both n-and p-doped GaAs the electric field of the space charge layer induces a strain that changes the crystal symmetry from cubic to orthorhombic [25][26][27][28][29]34]. The breakdown of the cubic symmetry gives rise to the pronounced LEO oscillation, as described above, which scales linearly with the integrated surface field and has been used as a measure for the SEF [14][15][16][17][18][19]33]. We therefore conclude the increase of the LEO oscillation (Fig.…”
Section: Interpretation and Discussionmentioning
confidence: 95%
“…It was shown that external uniaxial stress can cause a significant modification of the RAS signal around the E 1 , E 1 þ D 1 critical points [29]. Lastras-Martinez et al [28,33] determined the different contributions of the surface roughness and the strain induced by the surface dimers at undoped GaAs samples. In their work the roughness contribution was found to be rather structureless and small compared to the strain contribution.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Uniaxial strain lowers the symmetry of the material and can be detected with RAS [67,68]. Interpretation is relatively straightforward where an external stress is applied to the system, but care is required, for example, when measuring the strain induced by a surface reconstruction [69].…”
Section: Nanostructures and Solid-solid Interfacesmentioning
confidence: 99%